New records of Neotropical Pentatominae (Heteroptera: Pentatomidae) - Dellapé, Gimena (Entomological Communications, 2021)
The subfamily Pentatominae is the most diverse within Pentatomidae, with about 120 genera and 680 species recorded in the Neotropics. The genera Euschistus Dallas, 1851 and Glyphepomis Berg, 1891 and the species Banasa dolabrata Thomas, 1988, B. peruana Thomas, 1990, B. testacea Thomas, 1990, Glyphepomis setigera Kormilev & Pirán, 1952, and Euschistus taurulus Berg, 1878 are recorded for the first time in Paraguay; and two monotypic genera, Berecynthus Stål, 1862 and Nocheta Rolston, 1980, are recorded for the first time in Bolivia and Ecuador, respectively. These new records increase the known country level diversity of Pentatominae in the Neotropics.